2019
DOI: 10.1038/s41586-019-1032-7
|View full text |Cite
|
Sign up to set email alerts
|

Neoantigen-directed immune escape in lung cancer evolution

Abstract: Data Availability Sequence data used during the study will be deposited at the European Genome-phenome Archive (EGA), which is hosted by The European Bioinformatics Institute (EBI) and the Centre for Genomic Regulation (CRG) under the accession code: EGAS00001003458. Further information about EGA can be found at https://ega-archive.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
615
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 691 publications
(673 citation statements)
references
References 35 publications
22
615
1
1
Order By: Relevance
“…Whereas the majority of early studies have prioritized single TCRs recognizing targets in the context of the common HLA‐A*02:01 allele (of North American and European Caucasian populations), only recently have investigators searched for TCRs restricted to other common alleles 123 . Priority targeting of known driver mutations, which are more likely to be clonal “trunk” mutations, will be advantageous so as to limit immune escape from antigen loss or incomplete clearance due to preexisting intratumor heterogeneity 124–126 . A final consideration for effective NeoAg‐specific therapies is that of optimal TCR avidity.…”
Section: Considerations For Neoag‐specific Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the majority of early studies have prioritized single TCRs recognizing targets in the context of the common HLA‐A*02:01 allele (of North American and European Caucasian populations), only recently have investigators searched for TCRs restricted to other common alleles 123 . Priority targeting of known driver mutations, which are more likely to be clonal “trunk” mutations, will be advantageous so as to limit immune escape from antigen loss or incomplete clearance due to preexisting intratumor heterogeneity 124–126 . A final consideration for effective NeoAg‐specific therapies is that of optimal TCR avidity.…”
Section: Considerations For Neoag‐specific Therapiesmentioning
confidence: 99%
“…123 Priority targeting of known driver mutations, which are more likely to be clonal "trunk" mutations, will be advantageous so as to limit immune escape from antigen loss or incomplete clearance due to preexisting intratumor heterogeneity. [124][125][126] A final consideration for effective NeoAg-specific therapies is that of optimal TCR avidity. Studies employing minimally altered tumor epitopes to model varying TCR-MHC interaction strengths have demonstrated that vaccination with intermediate affinity epitopes provides optimal tumor control, whereas the highest affinity epitope vaccinations result in a dysfunctional T cell response.…”
Section: Considerations For Neoag-specific Therapiesmentioning
confidence: 99%
“…2,9 In order to stimulate an antitumor immune response, neoantigens must be presented to T cells in the context of MHC molecules. Numerous sources of TAAs and neoantigens arise due to mutation of oncogenes and suppressor genes, re-expression of foetal proteins and oncogenic viral proteins, and/ or overexpression of normal proteins.…”
Section: Neoantigens and Vaccinationmentioning
confidence: 99%
“…The intratumoral heterogeneity (ITH) consequently gives rise to subclonal neoantigens. The link between neoantigen clonality and ICI effects has been reported, indicating the necessity of targeting clonal but not subclonal cancer antigens to maximize the effects of immunotherapy …”
Section: Immunoediting Antigen Clonality and Immunogenicitymentioning
confidence: 99%
“…The link between neoantigen clonality and ICI effects has been reported, indicating the necessity of targeting clonal but not subclonal cancer antigens to maximize the effects of immunotherapy. 26,27 Another important aspect of neoantigen research is related to their immunogenicity. As every HLA ligand with an altered amino acid does not elicit host T-cell responses, clarification of the rules and elements defining immunogenicity is of great importance.…”
Section: Immunoediting Antigen Clonality and Immunogenicitymentioning
confidence: 99%